2003
DOI: 10.1111/j.1545-5300.2003.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Narratives About Their Children by Mothers Hospitalized on a Psychiatric Unit

Abstract: The diagnosis of "mental illness" is accompanied by negative implications regarding a person's competence. Self- and other-descriptions about the "patient" are embedded within broader cultural and societal discourses, influencing his/her relationships. The parental role seems to be one of the most sensitive, especially for women. Mothers hospitalized in psychiatric units often have to separate themselves from their children either temporarily, during hospitalization, or permanently, after a loss of custody. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 12 publications
4
71
0
8
Order By: Relevance
“…25 Another study found that 18 of 20 mothers hospitalized on an inpatient psychiatry unit had "coherent maternal narratives" of their children and fought to maintain contact, even when living apart. 17 Separation may thus be viewed as temporary by many mothers, or even integrated into a new kind of mother-child relationship, with anxiety symptoms and worry over the child predominating.…”
Section: Mothers With Mental Illnessmentioning
confidence: 99%
“…25 Another study found that 18 of 20 mothers hospitalized on an inpatient psychiatry unit had "coherent maternal narratives" of their children and fought to maintain contact, even when living apart. 17 Separation may thus be viewed as temporary by many mothers, or even integrated into a new kind of mother-child relationship, with anxiety symptoms and worry over the child predominating.…”
Section: Mothers With Mental Illnessmentioning
confidence: 99%
“…Many of the sources of parenting stress raised by parents with mental illness are generic to all parents, while others are specific to the situation of parents living with mental illness (Nicholson et al 1998). Issues that parents with mental illness have identified as specific to their situation include dealing with the stigma of mental illness, which limits their ability to freely discuss areas of concern, managing day-to-day parenting whilst managing mental illness, the side effects of medications that could impair their ability to parent (Savidou et al 2003) and social isolation (Nicholson et al 1998). Parents with mental illness are vulnerable to multiple stressors besides the risk associated directly with the mental illness: they are at high risk of living in poverty and have very low employment rates.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, studies describing how parents relate to their children, show that parents often felt tired, having difficulties in motivating themselves, which contributed to a low interaction with their children, and that one of the side effects of the medication was having trouble to concentrate (Evenson et al, 2008;Rampou et al, 2015). Nevertheless, several parents in the studies talked about how important their children were to them and how they strived to be a good parent Diaz-Caneja & Johnson, 2004;Evenson et al, 2008;Perera et al, 2014;Savvidou et al, 2003). They were stressed by the fact that when they, for example, needed to seek psychiatric care, they did not know how to handle the situation of the children (Evenson et al, 2008).…”
Section: Parenting and Mental Illnessmentioning
confidence: 99%